2017
DOI: 10.1111/pai.12824
|View full text |Cite
|
Sign up to set email alerts
|

The association between a genetic risk score for allergy and the risk of developing allergies in childhood—Results of the WHISTLER cohort

Abstract: Background: Several genetic variants have been associated with the susceptibility to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Several studies showed the association between the GRS for allergy and the risk of allergic diseases 28 . However, no study has explored the effect of dietary pattern on AR of children according to the GRS for allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed the association between the GRS for allergy and the risk of allergic diseases 28 . However, no study has explored the effect of dietary pattern on AR of children according to the GRS for allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…An appropriate AR therapy might improve children's quality of life and school productivity 11. These results might provide a clue to determine whether the improvement of dietary habits may be helpful to alleviate individual AR symptoms.Several studies showed the association between the GRS for allergy and the risk of allergic diseases 28. However, no study has explored the effect of dietary pattern on AR of children according to the GRS for allergic diseases.…”
mentioning
confidence: 99%
“…Second, genetic risk was classified based on the number of risk allele homozygotes, which did not fully consider the single effect of each risk allele on the disease and may weaken its role. The genetic risk score (GRS), an emerging method that integrates weak effects of each risk allele and enables valid causal estimates with large numbers of genetic variants, 25 has been widely used in genetic studies of complex diseases 26–28 . In our further research, more genes, and SNPs associated with allergy, as well as GRS, should be included.…”
Section: Discussionmentioning
confidence: 99%
“…It integrates weak effects of multiple SNPs and dramatically enhances the predictability of complex diseases using gene polymorphisms [30]. The GRS has been widely applied in genetic studies of common complex diseases, such as diabetes, coronary heart disease, asthma, and others [31][32][33]. The results from the Wheezing Illnesses Study Leidsche Rijn (WHISTLER) cohort illustrated that an adult-derived GRS for allergy predicted the risk of developing allergies during childhood [33].…”
Section: Associations Between the Loose And Stringent Api And Differementioning
confidence: 99%